Membangun Keunggulan Kompetitif Melalui Orientasi Pasar, Kreativitas Produk dan Inovasi Produk Pada IKM Kerajinan Kabupaten Bantul Yogyakarta - Andika Andika; Muinah Fadhilah; Ambar Lukitaningsih (Universitas Batanghari, 2021)
The purpose of this study was to address the gaps in the results of previous studies regarding the effect of market orientation and product creativity on competitive advantage by adding an intervening variable, namely product innovation. This research is located in Bantul Regency, involving 100 respondents who act as owners or managers of IKM Crafts. The sampling technique used was the method Consecutive Sampling. The model analysis technique and hypothesis testing used by researchers is the Partial Least Square (PLS) analysis with SmartPLS 3.3.3 software, while the mediation analysis uses the Sobel test. The results obtained in this study indicate that market orientation has a significant effect on product innovation and competitive advantage; Product creativity has a significant effect on product innovation but not significant on competitive advantage. The results of the single-test analysis show that product innovation is able to significantly mediate the effect of product creativity on competitive advantage but is unable to act as a mediator on the effect of market orientation on competitive advantage. The limitation of this research is that the data collected is limited to IKM Crafts in Bantul Regency. Practical Implications - Craft SMIs should consider the application of product innovation through market orientation and product creativity to build competitive advantage. When product innovation through market orientation and product creativity is implemented properly, competitive advantage can be achieved.